Poverty and Floods in Cap-Haïtien - World Bank (World Bank, Washington, DC, 2020)
Nested in a bay, the Cap-Haïtien, Haiti second largest city, is home to a large river basin characterized by rapid and uncontrolled urbanization and fears devastating floods during the rainy season. In Haiti, frequent and severe adverse natural events affect negatively households, and even more the poorest. In Cap-Haïtien, high structural vulnerability of infrastructure and high exposure to floods, increasing households’ vulnerability to falling into poverty traps. The purpose of this report is to describe the nature of floods in Cap-Haïtien and its relationship with poverty. The report is structured as follows, the authors begin with a brief literature review of the nexus between exposure, vulnerability and resilience to natural disasters, and poverty. In section 3, the authors describe the data beginning with the socio-economic characteristics of households in Cap-Haïtien including their demographics, nature of their dwellings, economic activities. In section 4, the authors examine the exposure of households to floods by describing the profiles of affected households. Section 5 examines the vulnerability of households to floods by using simple regressions to estimate the effects of floods on household welfare and the heterogeneity of the impact across households. In section 6, the authors examine households’ resilience to floods by describing the strategies used to prepare for and cope with floods. The concluding section focuses on implications of the results.